The constitution of the unilateral usufruct - Siguas Rivas, Julián (2019)
Subsection 2 of Article 1000 of the Civil Code establishes as a modality in the constitution of the Usufruct, the socalled Unilateral Usufruct; the same that is understood as the one constituted with the sole will of the owner of the good in favor of the usufructuary; declaration that is instrumented in a Public Deed, its transfer is sufficient title to register it; this is due to a lack of knowledge of the institution and its conceptual elements; being the ratio of the present article to establish what must be understood by Unilateral Constitution of Usufruct.